CONTRIBUTIONS AND LIMITATIONS OF THE TEACHING METHODS IN CHILDREN’S LITERACY - Gabriel, Rosangela (2010)
In order to improve reading and writing learning, the analysis of the teaching methods is of fundamental importance. According to Soares (2003, 2007), to highlight which are the best strategies to be used on teaching reading and writing to children, in order to offer all the conditions for the learner to be initiated in the literate world, it is necessary to analyze the literacy under three points of view. The first one concerns to the technical subject of the language, that is, the decoding and coding action, the conversion grapheme-phoneme/phoneme-grapheme. The second one focus attention on meaning, on reading comprehension, while the third point considers literacy a social process, that is, the learning of the written language possesses functions and objectives according to the social context in which it is inserted. Starting from that, this study was conceived with the intention of discussing the favorable and contrary arguments to the phonics and global methods in children’s literacy, with the aim of investigating which is the best way of teaching reading and writing. Besides the comparison of theoretical issues, interviews with first year’s school teachers about the teaching methods they adopt were conducted. The results suggest that both methods, the global and the phonics, present legitimate arguments concerning reading and writing teaching. Following that reasoning, it is wise to search for a balance in using the best of both methods. In order to reach literacy with quality, it is necessary to respect the students’ trajectory in the development of their hypotheses, to make possible the work with texts, to rescue the importance of teaching the alphabet and the relationships between sounds and letters, to respect the moments of discoveries of the learners, to present reading at the same time as a pleasure and as a fundamental tool in the social dynamics.